FACTORS THAT AFFECT THE ACCESS TO ENTREPRENEURSHIP FINANCE IN THE UK - ADESANYA, ADETOLA OPEOLUWA (2007)
The importance of entrepreneurship as a tool to economy growth and employment creation has generated a lot of interest from various quarters. The area I am interested in is the access to finance. Studies have shown that, access to finances is a major factor that informs the decision to be self-employed. There are various types of finances available to entrepreneur, but it comes with its peculiar constraints. This study is taken with an aim to provide an insight into what factors determines the kind of financing an entrepreneur would employ to finance its business and the form of constraint the entrepreneur may experience in accessing the various forms. Included is various efforts the UK government is doing to alleviate such constraint in a bid to encourage its survival albeit economy growth. Data are collected by interviews and survey questionnaire, the interviews are analysed in a case study form and the survey questionnaires are responded to by 18 entrepreneurs cutting across industry, age, sex and education. This paper has been able to identify some of the various factors that affect the access to start-up and growth capital of an entrepreneur. The research is conducted to give an overall view rather than a specific result about the research question dealt with. It has been to provide information about accessing finances for Entrepreneurs and percevied constraint from the view of entrepreneurs, with solutions recommended.